Camille Pissarro’s Late Self-Portraits and The Mirror Stage of Old Age - Gottlieb, Shira (Age, Culture, Humanities: An Interdisciplinary Journal, 2024)
This article analyzes the late self-portraits of French Impressionist painter Camille Pissarro (1830–1903) in light of Leni Marshall’s argument on the positive potential of misrecognition—the psychological outcome of Kathleen Woodward’s concept of the Mirror Stage of Old Age. Around the age of seventy, Pissarro, predominantly known as a landscape painter, was compelled to abandon working outdoors due to a chronic eye infection. Two of his three selfportraits from this period were executed with the aid of a mirror, depicting the artist in an interior setting with a window revealing an urban landscape. I suggest that Pissarro channels the physical limitations he faced due to age and health into new modes of production and expression, as conveyed in these portraits. Additionally, this article considers Pissarro’s self-portraits within the framework of Old Age Style, proposing that his adaptation to new practices represents a metamorphosis of OAS––not in traditional formalistic terms, but rather in terms of creativity and practice.